Techniques on video streaming for back pain prevention - Ramdan, Nur Sufiah Akmala; Bani Hashim, Ahmad Yusairi; Kamat, Seri Rahayu; Asmai, S. A. (Horizon Research Publishing, 2014)
This paper is about the study of techniques on multiple video streaming, which is going to be used to prevent back pain among manual workers. The method used in this study is by using multiple video streaming which consists of three important elements; webcams , SimpleCV open-source and Python language. There are three techniques to do the video analysis. First is by using “on-the-shelf” software, the second is by combining the “on-the-shelf” software and self-programming, and the third one is by developing the “in-house” programming. The pilot test was held in Manufacturing Engineering Faculty, Universiti Teknikal Malaysia Melaka. The aim of the pilot test is to know whether the system is successful or not and to upgrade the system if there are any weaknesses.